Estimation of livestock greenhouse gas for impact mitigation - D.S.I. Sondakh; F.R. Tulungen; J.K. Kampilong; F.S.J. Rumondor; Y.S. Kawuwung; E.P. Sanggelorang (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Anthropogenic activities in livestock sectors are responsible for emitting substantial amounts of greenhouse gases, including carbon dioxide, methane, and dinitrous oxide, into the atmosphere, thereby contributing to climate change. The impact of these gases can be reduced through effective mitigation and adaptation efforts. This study aimed to estimate the livestock greenhouse gas emissions in Minahasa District, Indonesia; identify the greenhouse gas sources and distribution; and provide feasible mitigation options.METHODS: This study used mixed methods to collect primary and secondary data from breeders and stakeholders in the Minahasa Regency. Interviews and questionnaires were also conducted, and the local government office provided secondary data. Breeders from various groups who lived in 25 different districts participated in this study, and the data analysis techniques used a Tier 1 model to process the data. The participants were included in focus group discussion activities for qualitative data collection to formulate potential mitigation strategies.FINDINGS: The livestock sector emitted 48.83 gigagrams of carbon dioxide equivalent in 2021, and this was expected to increase by 24.98 percent in 2022, resulting in a total emission of 65.09 gigagrams of carbon dioxide equivalent. The sector also experienced a steady rise in emissions since 2010, with an average annual increase of 3.17 percent. The emissions were primarily composed of methane and dinitrous oxide, which accounted for 64.68 and 0.41 gigagrams carbon dioxide equivalent, respectively. In terms of livestock greenhouse gas distribution, the Sonder District produced 13.98 percent of the emission at 8.77 gigagrams of carbon dioxide equivalent. The main emissions resulted from methane manure management and enteric fermentation at 84.53 and 15.23 percent (7.41 and 1.34 gigagrams of carbon dioxide equivalent, respectively), while the remaining was composed of dinitrous oxide gas. In Kawangkoan District, the greenhouse gas emissions were dominated by methane from enteric fermentation and manure management, which accounted for 15.23 and 20.05 percent (5.63 and 1.43 gigagrams of carbon dioxide equivalent). In addition, the total emission accounted for 11.33 percent at 7.11 gigagrams of carbon dioxide equivalent.CONCLUSION: The study produced an estimate of greenhouse gases from the livestock sector in the Minahasa Regency. During the studied period (2010-2022), the total greenhouse gas emissions exhibited an average annual increase of 3.17 percent. In 2022, the emissions consisted of methane and dinitrous oxide, with respective contributions of 99.38 percent per year and 0.62. Based on the spatial mapping, the Sonder District produced the largest cumulative emissions, primarily driven by emissions from animal waste management. Conversely, the Kawangkoan District dominated emissions stemming from the enteric fermentation of ruminant animals. These findings imply that all stakeholders in the Minahasa Regency should prioritize efforts to implement adaptation and mitigation programs to reduce these impacts.